SARS-CoV-2 infection during pregnancy and pregnancy-related conditions: Concerns, challenges, management and mitigation strategies-a narrative review - Rakesh Kumar; Cut Meurah Yeni; Niken Asri Utami; Rupali Masand; Rajesh Kumar Asrani; Shailesh Kumar Patel; Akshay Kumar; Mohd. Iqbal Yatoo; Ruchi Tiwari; Senthilkumar Natesan; Kranti Suresh Vora; Firzan Nainu; et al. (Elsevier, 2021)
The ongoing coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a global public health problem. The SARS-CoV-2 triggers hyper-activation of inflammatory and immune responses resulting in cytokine storm and increased inflammatory responses on several organs like lungs, kidneys, intestine, and placenta. Although SARS-CoV-2 affects individuals of all age groups and physiological statuses, immune-compromised individuals such as pregnant women are considered as a highly vulnerable group. This review aims to raise the concerns of high risk of infection, morbidity and mortality of COVID-19 in pregnant women and provides critical reviews of pathophysiology and pathobiology of how SARS-CoV-2 infection potentially increases the severity and fatality during pregnancy. This article also provides a discussion of current evidence on vertical transmission of SARS-CoV-2 during pregnancy and breastfeeding. Lastly, guidelines on management, treatment, preventive, and mitigation strategies of SARS-CoV-2 infection during pregnancy and pregnancy-related conditions such as delivery and breastfeeding are discussed.